2001
DOI: 10.1521/suli.31.2.207.21508
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation, Psychiatric Disorder, and Medical Illness in a Community Epidemiological Study

Abstract: Many epidemiological studies have analyzed suicidal ideation in clinical samples, but only a few have been performed in the general population. We present the results of a two-stage epidemiological study in the general population on the island of Formentera (Balearic Islands, Spain), which used the 28-item General Health Questionnaire (GHQ-28) in the first stage (n = 697) and the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) in the second (n = 242). We also recorded medical illnesses diagnosed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 19 publications
2
34
3
5
Order By: Relevance
“…The Spanish rate obtained by us was the one exception as it was somewhat lower than the 6.5% rate found in the study on the Spanish island of Formentera [9] while our rates for Finland are broadly in line with those of another study [6] in that country.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The Spanish rate obtained by us was the one exception as it was somewhat lower than the 6.5% rate found in the study on the Spanish island of Formentera [9] while our rates for Finland are broadly in line with those of another study [6] in that country.…”
Section: Discussionsupporting
confidence: 83%
“…These figures are much lower than their nearest equivalent, suicidal plans, (1.1-15.6) reported in one study 9 . It is also noteworthy that suicidal plans were identified at all sites in that study whilst active suicide intent (SI 4), its nearest equivalent in our study, is only present in the Scandinavian and Spanish sites.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Suicide ideation is considered by some to be the first step toward suicide (Gili-Planas et al, 2001); it is one of the strongest predictors of a future suicide attempt in adolescents and is related to risk of completed suicide (Brent et al, 1993;Lewinsohn et al, 1996;Reinherz et al, 1995). The current public health significance of suicidal thoughts and behaviors is large in the United States and globally (Murray and Lopez, 1996;United States Public Health Service, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, growing evidence has suggested that suicide can be conceptualized as motivated by the desire to escape from unbearable psychological pain (Durkheim, Spaulding, & Simpson, 2010).In depressed individuals, the decreased ability to experience pleasure incombination with a strong motivation to relieve pain can lead to maladaptive behavioral disinhibiting and an increased likelihood of suicide attempts. Furthermore, hopelessness, or believing future outcomes will be negative rather than positive, is one of the most prominent cognitive factors associated with depression (Abramson, Alloy, 1998;Abramson, Metalsky, & Alloy, 1989;Romens, Abramson, & Alloy, 2009;Hawton, Casanas, Haw, Saunders, 2013) and suicidality (Harris, Barraclough, 1997;Gili-Planas, Roca-Bennasar, Ferrer-Perez, Bernardo-Arroyo, 2001;Christensen,Batterham, Soubelet, & Mackinnon, 2013).Therefore, regarding suicides with help, the opinion that a person who chooses death can reflect on his situation constructively, and he is still capable to experience positive emotions, is not evidence -based. Nonetheless, supplementary research is needed to explore further the different factors contributing to unwillingness to live which is a sign of diminished psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%